The Reflection of Non-Verbal Means of Communication in Written Speech - Musayeva Gulistan Kosbergenovna (Academia One Publishing, 2023)
This article explores the problems of the emergence of new non-verbal means of communication in the social networks of the Internet. In the projection of historical development, the reasons for their appearance, formation and dynamics of development are shown.
Keywords: communication; writing; emoticons; emoji